الأحزاب السياسية كآلية لتشكيل النظم الدستورية: دراسة في التأثير المتبادل والتفاعلات المؤسسية (Comprehensive Journal of Science, 2025)
This research paper examines the interactive relationship between political parties and contemporary constitutional systems, considering political parties as key actors in political life and as a fundamental link between the state and society. The study aims to analyze the institutional and political role of parties in shaping constitutional systems, particularly in terms of legislation-making, the balance of powers, and the achievement of political stability. It also seeks to highlight how these systems are influenced by the nature of the prevailing party system, while shedding light on the differences between presidential, parliamentary, and semi-presidential systems.The study is based on the hypothesis that the strength of political parties, their internal organization, and their level of interaction with society have a direct impact on the effectiveness and stability of the constitutional system. It adopts the descriptive-analytical, comparative, and historical approaches, which together allow for a deeper understanding of the evolution of the relationship between political parties and constitutions, as well as the challenges facing this relationship, particularly in developing countries or those undergoing constitutional transitions. The study contributes to enriching the academic debate on the role of political parties as a central pillar in building modern constitutional systems and enhancing their performance